Low Self-Esteem and Its Association With Anxiety, Depression, and Suicidal Ideation in Vietnamese Secondary School Students: A Cross-Sectional Study - Nguyen, Dat Tan; Wright, E. Pamela; Dedding, Christine; Pham, Tam Thi; Bunders, Joske (Frontiers in Psychiatry, 2019)
Background: There is a correlation between self-esteem in adolescents and risks and protective factors for their health and welfare. The study was conducted to determine the prevalence of low self-esteem and socio-demographic features related to anxiety, depression, educational stress, and suicidal ideation in secondary school students in Vietnam. Method: A cross-sectional design was employed for this study with participation of 1149 students in Cantho City in Vietnam. A structured questionnaire was applied to ask about self-esteem, depression, anxiety, educational stress, and suicidal ideation. Results: Students with low self-esteem were detected at a prevalence of 19.4%. High educational stress, and physical and emotional abuse by parents or other adults in the household were major risk factors correlated to low self-esteem, while a protective factor for low self-esteem was attending supplementary classes. An association among lower self-esteem and increased anxiety, depression, and suicidal ideation was detected. Conclusions: Self-esteem is associated with anxiety, depression, and academic stress, which significantly affect students’ quality of life and links to suicidal ideation. These results therefore suggested the need for a school-based or web-based provision aimed at proactively increasing students’ self-esteem, and skills for dealing with academic stress.